Stack optimization of oxide-based RRAM for fast write speed (<1 μs) at low operating current (<10 μA). (November 2016) - Chen, C.Y.; Goux, L.; Fantini, A.; Degraeve, R.; Redolfi, A.; Groeseneken, G.; Jurczak, M.
Abstract: In this paper we engineer a TiN ⧹ Al2 O3 ⧹ (Hf, Al)O2 ⧹ Ta2 O5 ⧹ Hf Oxide Resistive Random Access Memory (OxRRAM) device for fast switching at low operation current without sacrificing the retention and endurance properties. The integrated 40 nm × 40 nm cell switches at 10 μA using write pulses shorter than 100 ns (resp. 1 μs) for Reset (resp. Set) and with amplitude <2 V. Using these conditions in a specially developed verify algorithm, a resistive window of 10× is reliably obtained, decreasing the write speed by more than 1 decade compared to state-of-the-art OxRRAM stacks at same current level.